Teachers’ perceptions of remote learning during the pandemic: a case study - Silva, Susana (2022)
The closure of higher education institutions (HEIs) due to the outbreak of the COVID-19 pandemic led to visible changes in pedagogical practices. With the lockdown, there was ambiguity and disagreement about the workload of teachers and students, and about what to teach and what strategies to select. For most instructors, the first challenge was to recreate the face-to-face experience. Worldwide, most universities have speedily adopted synchronous and asynchronous communication modes. Google Classroom, Microsoft Teams, Cisco, Webex, Zoom, and Moodle were among the most used tools. The present study is based upon a quantitative approach, and it intends to analyse teachers’ perceptions of remote teaching during the first pandemic period. Data were collected through an online questionnaire during June and July 2020. The questionnaire had 27 questions divided into three main sections: sociodemographic characterization, e-Learning strategies, and remote assessment. The study population was teachers of a Portuguese HEI. A random sample was used with 547 participants. The main conclusions show that the less experienced teachers are, the more satisfied they feel with remote classes and remote assessment. On the other hand, the most experienced teachers used more tools during the remote teaching period and developed more strategies to perform remote assessment. Regarding the overall assessment of the emergency remote teaching, the participants consider that it was a positive period, and they were moderately satisfied with remote classes and the strategies and tools used during this period.